Spraying-free imitation metal master batch, extrusion spraying-free ABS alloy material and preparation method of extrusion spraying-free ABS alloy material
By covering the alloying silica and co -gathered linked with polypropylene pheasant on the surface of the aluminum pigment to form a polyhedron -free imitation imitation metal female granules, solve the melting line of the current imitation metal spray -free materials, and the hemp point concave. The problem of insufficient pits and metal texture significantly improves the metal texture and performance of ABS alloy materials.
Patent Information
- Application Number
- CN202510001718.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing imitation metal spray-free materials in the market have problems such as flow mark weld wire, pit pits and weak metal texture.
Through the surface of the aluminum pigment surface, it is used to co-cross the cross-linking with polypropylene to form a network structure of O-SI-O functional groups and cyanomy, and obtains silicon-polypropylene compound nano-balls. This composite nano -micro -ball forms a layered structure through die casting. After grinding and polishing, the polygonal structure is used to obtain the polygonal structure.
This method eliminates defects such as the melting line of flow marks and the pits of hemp point, improves the metal texture effect of squeezing out of the metal materials for spray -free ABS alloy materials, and enhancing the mechanical performance and stable performance of the material.
Smart Images

Figure CN119371767A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a spray-free imitation metal masterbatch and an extruded spray-free ABS alloy material and a preparation method thereof. Background Art
[0002] ABS resin material is a terpolymer of acrylonitrile (A), butadiene (B), and styrene (S). The relative content of the three monomers can be changed arbitrarily to make various resins. As one of the five general synthetic plastics, ABS resin has the unique properties of ABS resin material, which makes it chemical resistant, low temperature resistant and impact resistant, and has excellent processing performance. Therefore, ABS resin material can be used in all walks of life. Among them, due to the good dimensional stability and high-gloss appearance aesthetic performance of ABS resin material, most consumer products such as home appliances and electronic appliances still use ABS resin material as the shell of product parts. With the gradual upgrading of the aesthetic requirements of home appliances, metal texture has gradually become the main trend of home appliance appearance design.
[0003] Because of its excellent appearance, economic and environmental protection, spray-free metal texture plastics have been used in home appliances, automobiles, 3C, daily necessities, and building materials, and have been widely praised by the market. Figure 1 , Figure 2 As shown, the problems of flow marks, weld lines, pitting and pits on the surface of the imitation metal spray-free materials currently on the market cannot be solved. At the same time, the metal texture is weak and there are appearance defects. Summary of the invention
[0004] Based on this, the purpose of the present invention is to provide a spray-free imitation metal masterbatch and an extruded spray-free ABS alloy material and a preparation method thereof, so as to solve the defects of flow marks, weld lines, pits, and weak metal texture in the existing imitation metal spray-free materials on the market.
[0005] To achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a spray-free imitation metal masterbatch, characterized in that it comprises the following steps: S1. After mixing the silane coupling agent with anhydrous ethanol, adding ammonia, aluminum pigment, and tetraethyl orthosilicate, stirring and mixing under a protective atmosphere, heating the reaction, filtering, washing, and drying to obtain a modified silica-coated aluminum pigment; S2. The modified silica-coated aluminum pigment is copolymerized and cross-linked with a polyacrylonitrile resin to obtain silica-polyacrylonitrile composite nanospheres; S3. The silicon dioxide-polyacrylonitrile composite nano-microspheres are die-cast to form a layered aluminum sheet, and the aluminum sheet is ground, polished, and sieved to obtain a spray-free imitation metal masterbatch with a polyhedral structure.
[0006] The surface of the spray-free imitation metal masterbatch prepared by the present invention has very strong polarity, and can be tightly combined with ABS resin through hydrogen bonds, thereby ensuring complete interface compatibility between aluminum powder and ABS resin; at the same time, the spray-free imitation metal masterbatch is a polyhedron structure, has multiple reflective surfaces, and the reflective effect of each surface is almost the same, which can avoid the problem of corner discoloration and fundamentally improve defects such as flow marks and weld lines; the present invention eliminates defects such as flow marks and weld lines, pits and pits caused by uneven dispersion of metal powder and agglomeration of melt flowing metal powder during molding and injection molding, and improves the metal texture effect of extruded spray-free ABS alloy materials.
[0007] As a further improvement of the above solution of the present invention, in step S1, the silane coupling agent includes at least one of methyltriethoxysilane, acryltetraethoxysilane, and dimethyldimethoxysilane.
[0008] As a further improvement of the above scheme of the present invention, the silane coupling agent includes methyltriethoxysilane, acryltetraethoxysilane and dimethyldimethoxysilane, and the volume ratio of the methyltriethoxysilane, the acryltetraethoxysilane and the dimethyldimethoxysilane is 1~3:1:1.
[0009] As a further improvement of the above scheme of the present invention, in step S1, the usage ratio of the silane coupling agent, anhydrous ethanol, ammonia water, aluminum pigment and tetraethyl orthosilicate is 3-8 g: 200-550 mL: 5-15 mL: 5-10 g: 4-8 g, and the concentration of the ammonia water is 25%.
[0010] As a further improvement of the above scheme of the present invention, in step S1, the heating reaction is stirred at 40-60° C. for 2-4 hours, and the drying is dried in a vacuum environment at 80-85° C. for 5-7 hours.
[0011] As a further improvement of the above scheme of the present invention, in step S2, the copolymerization and cross-linking reaction includes the following steps: adding the modified silica-coated aluminum pigment into deionized water and mixing evenly, adding polyacrylonitrile resin, heating and stirring, and then adding an initiator and a cross-linking agent and continuously stirring. After the reaction is completed, cooling to room temperature, filtering, washing, and drying to obtain silica-polyacrylonitrile composite nanospheres.
[0012] As a further improvement of the above scheme of the present invention, in the copolymerization and cross-linking reaction, the usage ratio of the modified silica-coated aluminum pigment, polyacrylonitrile resin, initiator, and cross-linking agent is 70~120mg:3~6mL:60~100mg:150~200mg, the molecular weight of the polyacrylonitrile resin is 100,000~300,000, the heating and stirring is stirring at 80~95°C for 2~4h, and the drying is drying at 80~85°C in a vacuum environment for 5~7h.
[0013] As a further improvement of the above solution of the present invention, in step S3, the thickness of the aluminum sheet is 80-300 μm; And / or, in step S3, the screening is performed by a combined screening process of a linear vibrating screen and a sieve to obtain a spray-free imitation metal masterbatch with a polyhedral structure and a particle size of 50 to 120 μm.
[0014] The present invention also provides a spray-free imitation metal masterbatch, which is prepared by the method for preparing the spray-free imitation metal masterbatch as described above.
[0015] The present invention also provides an extruded spray-free ABS alloy material, which is prepared from the following components in parts by weight: 70-90 parts of ABS resin, 5-15 parts of the aforementioned spray-free imitation metal masterbatch, 2-8 parts of a toughening agent, 1-3 parts of a compatibilizer, 0.1-0.5 parts of a weathering agent, 0.2-1 parts of an antioxidant, 0.2-1 parts of a lubricant, and 0.5-2 parts of a dispersant.
[0016] As a further improvement of the above scheme of the present invention, the ABS resin is an acrylonitrile-butadiene-styrene copolymer, and the acrylonitrile-butadiene-styrene copolymer is obtained by mixing an acrylonitrile-butadiene-styrene copolymer prepared by an emulsion method and an acrylonitrile-butadiene-styrene copolymer prepared by a bulk method in a mass ratio of 3:1.
[0017] As a further improvement of the above scheme of the present invention, the toughening agent is a styrene-ethylene-butylene-styrene block copolymer; and / or the compatibilizer is a carboxylic acid grafted compatibilizer; and / or the antioxidant is a hindered phenol antioxidant; and / or the lubricant is lubricant TAS-2A; and / or the dispersant is a polymethacrylic acid derivative dispersant; and / or the weathering agent is a benzotriazole weathering agent.
[0018] The present invention also provides a method for preparing the above-mentioned extruded spray-free ABS alloy material, which comprises the following steps: in a protective atmosphere, ABS resin, a toughening agent, a compatibilizer, a weathering agent, an antioxidant, a lubricant and a dispersant are mixed uniformly in proportion, and then added to the main feeding port of an extruder, and the spray-free imitation metal masterbatch is added to the side feeding port of the extruder in proportion, and the extruded spray-free ABS alloy material is obtained through melt blending and extrusion granulation.
[0019] As a further improvement of the above scheme of the present invention, the ABS resin, toughening agent, compatibilizer, weathering agent, antioxidant, lubricant and dispersant are mixed at a temperature of 80° C. to 100° C. and a mixing time of 2 to 4 hours.
[0020] As a further improvement of the above solution of the present invention, the extruder is a twin-screw extruder, the barrel temperature of the extruder is 200° C. to 230° C., the screw speed is 200 to 300 rpm, and the vacuum degree is 0.06 to 0.1 MPa.
[0021] As a further improvement of the above solution of the present invention, the middle position of the extruder is provided with a TME element and a ZME element, and the head position is provided with a toothed disk. Both the TME element and the ZME element are dispersed combined thread elements, which can significantly improve the mixing uniformity and processing efficiency of the materials.
[0022] Compared with the prior art, the present invention has the following beneficial effects: 1. The spray-free imitation metal masterbatch provided by the present invention is prepared by hydrolyzing and polycondensing tetraethyl orthosilicate (TEOS) and a silane coupling agent under alkaline conditions, thereby coating the surface of an aluminum pigment with silica modified by a silane coupling agent; then copolymerizing and cross-linking the aluminum pigment coated with the modified silica with polyacrylonitrile, thereby forming a network structure of O-Si-O functional groups and cyano groups interwoven on the surface of the aluminum pigment, and the obtained silica-polyacrylonitrile composite nano-microspheres have a very strong polarity on the surface, thereby improving the dispersibility of the aluminum pigment in the resin; then die-casting the silica-polyacrylonitrile composite nano-microspheres to form a layered structure, and then grinding and polishing, so that the finally obtained spray-free imitation metal masterbatch is a polyhedral structure with multiple reflective surfaces and the reflective effect of each surface is almost the same.
[0023] 2. When the spray-free imitation metal masterbatch prepared by the present invention is introduced into the extruded spray-free ABS alloy material, since the surface of the spray-free imitation metal masterbatch has very strong polarity, it can be tightly combined with the ABS resin through hydrogen bonds, thereby ensuring complete interface compatibility between the aluminum powder and the ABS resin; at the same time, since the spray-free imitation metal masterbatch has multiple reflective surfaces and the reflective effect of each surface is almost the same, the problem of corner discoloration can be avoided, and defects such as flow marks and weld lines can be fundamentally improved; the present invention eliminates defects such as flow marks and weld lines, pits and pits caused by uneven dispersion of metal powder and agglomeration of melt flowing metal powder during molding and injection molding, and improves the metallic texture effect of the extruded spray-free ABS alloy material. The network structure of O-Si-O functional groups and cyano groups in the spray-free imitation metal masterbatch can effectively prevent chemical reagents such as oil stains from reacting with rubber molecules to cause aging, and can improve the mechanical properties and stability of the extruded spray-free ABS alloy material. In addition, Si-O in the spray-free imitation metal masterbatch has a higher bond energy and greater chemical inertness, and can improve the high and low temperature deformation resistance of the extruded spray-free ABS alloy material.
[0024] 3. When preparing the extruded spray-free ABS alloy material, the twin-screw extruder used in the present invention is provided with a TME element and a ZME element at the middle position and a toothed disk at the head position, which greatly improves the dispersion effect, solves the problem of pitting and pitting that is very easy to occur in traditional extrusion surface spraying, improves the production yield, and improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is an electron microscope picture of the existing extrusion spray-free materials on the market; Figure 2 This is the appearance picture of the existing extrusion spray-free material products on the market; Figure 3 This is an electron microscope image of the layered aluminum sheet obtained in Example 2; Figure 4 This is an electron microscope image of the spray-free imitation metal masterbatch prepared in Example 2; Figure 5 This is an electron microscope image of the extruded spray-free ABS alloy material of Example 2; Figure 6 This is an appearance picture of the extruded spray-free ABS alloy material product of Example 2. DETAILED DESCRIPTION
[0026] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0028] The raw material information used in the following examples and comparative examples of the present invention is as follows: ABS resin: obtained by mixing Chimei 749SK (emulsion method) and Takahashi 725 (bulk method) from Taiwan, China at a mass ratio of 3:1; Toughening agent: G1650MU, produced by Kraton, USA; Compatibilizer: CMG7000, produced by Jiayirong; Weathering agent: 384-2, produced by BASF; Antioxidant: Antioxidant 1010, very easy to produce; Lubricant: TAS-2A, produced by Suzhou Xingtai Guoguang; Dispersant: EFKA-4401, produced by Efka; Methyltriethoxysilane: YJ-69, produced by Shandong Yuanjin; Propylene tetraethoxysilane: produced by Hubei Jianghao; Dimethyldimethoxysilane: produced by Shandong Yuanjin; Deionized water: produced by RO reverse osmosis method; Ammonia water: 25% concentration, commercially available; Aluminum pigment: PCR901, produced by AiKa; Ethyl orthosilicate: analytical grade, Shantou Guanghua Chemical Factory; Anhydrous ethanol: produced by Shandong Mingxin Chemical; 3-(Trimethoxysilyl)propyl methacrylate: produced by Beijing Lvyuan Bird; Polyacrylonitrile resin: NF2200, produced by Formosa Chemical Corporation in Taiwan, China; Initiator: 231-781-8, produced by Shandong Century Tongda; Cross-linking agent: VT859, produced by Hebei Pinke Biotechnology Co., Ltd. Commercially available metal masterbatch: PE1106, produced by Jincheng.
[0029] The above raw materials are only for illustrating the sources and components of the reagents used in the experiments of the present invention so as to fully disclose the information, and do not mean that the present invention cannot be realized by using other similar reagents or reagents provided by other suppliers.
[0030] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the present technical field.
[0031] Example 1 The present embodiment provides an extruded spray-free ABS alloy material, which includes the following component raw materials in parts by weight: 70 parts of ABS resin, 5 parts of spray-free imitation metal masterbatch, 2 parts of toughening agent, 1 part of compatibilizer, 0.1 part of weathering agent, 0.2 part of antioxidant, 0.2 part of lubricant and 0.5 part of dispersant.
[0032] The preparation method of the extruded spray-free ABS alloy material of the present embodiment comprises the following steps: in a nitrogen atmosphere, ABS resin, toughening agent, compatibilizer, weathering agent, antioxidant, lubricant and dispersant are mixed uniformly at 80°C for 4 hours in proportion, and then added from the main feeding port of the twin-screw extruder, and the spray-free imitation metal masterbatch is added from the side feeding port of the twin-screw extruder in proportion, and the barrel temperature of the twin-screw extruder is controlled to be 200°C, the screw speed is 200rpm, and the vacuum degree is 0.1MPa, and the extruded spray-free ABS alloy material is obtained through melt blending and extrusion granulation. Among them, the middle position of the twin-screw extruder of the present embodiment is provided with a TME element and a ZME element, and the head position is provided with a toothed disk.
[0033] The method for preparing the spray-free imitation metal masterbatch of this embodiment comprises the following three steps S1-S3: S1. A silane coupling agent (prepared by mixing methyltriethoxysilane, acryltetraethoxysilane and dimethyldimethoxysilane in a mass ratio of 1:1:1) was mixed with anhydrous ethanol, and ammonia water (concentration of 25%), aluminum pigment and tetraethyl orthosilicate were added, and the mixture was stirred for 1 hour under a nitrogen atmosphere, and then the temperature was raised to 60°C and stirred for 3 hours, wherein the amount ratio of the silane coupling agent, anhydrous ethanol, ammonia water, aluminum pigment and tetraethyl orthosilicate was 3g:200mL:5mL:5g:4g; after the reaction was completed, the mixture was filtered, and the product was washed three times with anhydrous ethanol, and then dried at 80°C in a vacuum environment for 6 hours to obtain a modified silica-coated aluminum pigment; S2. The modified silica-coated aluminum pigment obtained in step S1 is subjected to copolymerization and cross-linking reaction with polyacrylonitrile resin to obtain silica-polyacrylonitrile composite nano-microspheres. The specific process is: add the modified silica-coated aluminum pigment to deionized water and stir evenly, add polyacrylonitrile resin, stir at 85°C for 3h, add initiator and cross-linking agent and continue stirring, wherein the amount ratio of modified silica-coated aluminum pigment, polyacrylonitrile resin, initiator and cross-linking agent is 70mg:3mL:60mg:150mg; after the reaction is completed, cool to room temperature, filter, wash the product three times with anhydrous ethanol, and then dry it at 80°C in a vacuum environment for 6h to obtain silica-polyacrylonitrile composite nano-microspheres.
[0034] S3. The silicon dioxide-polyacrylonitrile composite nano-microspheres obtained in step S2 are die-casted to form a layered aluminum sheet with a thickness of 80-300 μm, the aluminum sheet is put into a ball mill for grinding, and then put into a magnetic polishing machine with a rotation speed of 800 r / s for polishing, and finally sieved by a combined screening process of a linear vibrating screen and a sieve screen to sieve out a spray-free imitation metal masterbatch with a polyhedral structure with a particle size of 50-120 μm.
[0035] Example 2 The present embodiment provides an extruded spray-free ABS alloy material, which includes the following component raw materials in parts by weight: 75 parts of ABS resin, 8 parts of spray-free imitation metal masterbatch, 4.5 parts of toughening agent, 1.5 parts of compatibilizer, 0.2 parts of weathering agent, 0.3 parts of antioxidant, 0.3 parts of lubricant and 1 part of dispersant.
[0036] The preparation method of the extruded spray-free ABS alloy material of the present embodiment comprises the following steps: in a nitrogen atmosphere, ABS resin, toughening agent, compatibilizer, weathering agent, antioxidant, lubricant and dispersant are mixed uniformly at 85°C for 2.5 hours in proportion, and then added from the main feeding port of the twin-screw extruder, and the spray-free imitation metal masterbatch is added from the side feeding port of the twin-screw extruder in proportion, and the barrel temperature of the twin-screw extruder is controlled to be 210°C, the screw speed is 220rpm, and the vacuum degree is 0.08MPa, and the extruded spray-free ABS alloy material is obtained through melt blending and extrusion granulation. Among them, the middle position of the twin-screw extruder of the present embodiment is provided with a TME element and a ZME element, and the head position is provided with a toothed disk.
[0037] The method for preparing the spray-free imitation metal masterbatch of this embodiment comprises the following three steps S1-S3: S1. A silane coupling agent (prepared by mixing methyltriethoxysilane, acryltetraethoxysilane and dimethyldimethoxysilane in a mass ratio of 2:1:1) was mixed with anhydrous ethanol, and ammonia water (concentration of 25%), aluminum pigment and tetraethyl orthosilicate were added, and the mixture was stirred for 1 hour under a nitrogen atmosphere, and then the temperature was raised to 60°C and stirred for 3 hours, wherein the amount ratio of the silane coupling agent, anhydrous ethanol, ammonia water, aluminum pigment and tetraethyl orthosilicate was 4g:300mL:8mL:6g:5g; after the reaction was completed, the mixture was filtered, and the product was washed three times with anhydrous ethanol, and then dried at 80°C in a vacuum environment for 6 hours to obtain a modified silica-coated aluminum pigment; S2. The modified silica-coated aluminum pigment obtained in step S1 is subjected to copolymerization and cross-linking reaction with polyacrylonitrile resin to obtain silica-polyacrylonitrile composite nano-microspheres. The specific process is: add the modified silica-coated aluminum pigment to deionized water and stir evenly, add polyacrylonitrile resin, stir at 85°C for 3h, add initiator and cross-linking agent and continue stirring, wherein the amount ratio of modified silica-coated aluminum pigment, polyacrylonitrile resin, initiator and cross-linking agent is 90mg:4mL:70mg:160mg; after the reaction is completed, cool to room temperature, filter, wash the product three times with anhydrous ethanol, and then dry it at 80°C in a vacuum environment for 6h to obtain silica-polyacrylonitrile composite nano-microspheres.
[0038] S3. The silica-polyacrylonitrile composite nanospheres obtained in step S2 are formed into a layered aluminum sheet having a thickness of 80 to 300 μm by die casting. Figure 3is an electron microscope image of the aluminum sheet in this embodiment, Figure 3 It can be seen that after die-casting, the aspect ratio of the aluminum sheet has changed greatly and can be close to 1:1; the aluminum sheet is put into a ball mill for grinding, and then put into a magnetic polishing machine with a rotation speed of 800r / s for polishing, and finally screened by a combined screening process of a linear vibrating screen and a sieve screen to screen out a polyhedral structure of a spray-free imitation metal masterbatch with a particle size of 50~120μm.
[0039] Figure 4 The electron microscope image of the spray-free imitation metal masterbatch prepared in this embodiment is shown in FIG. Figure 4 It can be seen that the appearance of the spray-free imitation metal masterbatch is a polyhedron, and the reflection of each surface is similar, and there will be no corner discoloration phenomenon; Figure 5 This is an electron microscope image of the extruded spray-free ABS alloy material prepared in this embodiment. Figure 5 It can be seen that the metal powder of the extruded spray-free ABS alloy material of this embodiment is evenly distributed without any defective points; Figure 6 This is a product appearance picture made of the extruded spray-free ABS alloy material prepared in this embodiment. Figure 6 It can be seen that the surface of the product is bright and has no defects.
[0040] Example 3 The present embodiment provides an extruded spray-free ABS alloy material, which includes the following component raw materials in parts by weight: 80 parts of ABS resin, 10 parts of spray-free imitation metal masterbatch, 5 parts of toughening agent, 2 parts of compatibilizer, 0.3 parts of weathering agent, 0.5 parts of antioxidant, 0.5 parts of lubricant and 1.2 parts of dispersant.
[0041] The preparation method of the extruded spray-free ABS alloy material of the present embodiment comprises the following steps: in a nitrogen atmosphere, ABS resin, toughening agent, compatibilizer, weathering agent, antioxidant, lubricant and dispersant are mixed uniformly at 90°C for 3h in proportion, and then added from the main feeding port of the twin-screw extruder, and the spray-free imitation metal masterbatch is added from the side feeding port of the twin-screw extruder in proportion, and the barrel temperature of the twin-screw extruder is controlled to be 220°C, the screw speed is 250rpm, and the vacuum degree is 0.08MPa, and the extruded spray-free ABS alloy material is obtained through melt blending and extrusion granulation. Among them, the middle position of the twin-screw extruder of the present embodiment is provided with a TME element and a ZME element, and the head position is provided with a toothed disk.
[0042] The method for preparing the spray-free imitation metal masterbatch of this embodiment comprises the following three steps S1-S3: S1. A silane coupling agent (prepared by mixing methyltriethoxysilane, acryltetraethoxysilane and dimethyldimethoxysilane in a mass ratio of 3:1:1) was mixed with anhydrous ethanol, and ammonia water (concentration of 25%), aluminum pigment and tetraethyl orthosilicate were added, and the mixture was stirred for 1 hour under a nitrogen atmosphere, and then the temperature was raised to 60°C and stirred for 3 hours, wherein the amount ratio of the silane coupling agent, anhydrous ethanol, ammonia water, aluminum pigment and tetraethyl orthosilicate was 5g:400mL:10mL:8g:6g; after the reaction was completed, the mixture was filtered, and the product was washed three times with anhydrous ethanol, and then dried at 80°C in a vacuum environment for 6 hours to obtain an aluminum pigment coated with modified silica; S2. The modified silica-coated aluminum pigment obtained in step S1 is subjected to copolymerization and cross-linking reaction with polyacrylonitrile resin to obtain silica-polyacrylonitrile composite nano-microspheres. The specific process is: add the modified silica-coated aluminum pigment to deionized water and stir evenly, add polyacrylonitrile resin, stir at 85°C for 35h, add initiator and cross-linking agent and continue stirring, wherein the amount ratio of modified silica-coated aluminum pigment, polyacrylonitrile resin, initiator and cross-linking agent is 100mg:4.5mL:80mg:180mg; after the reaction is completed, cool to room temperature, filter, wash the product three times with anhydrous ethanol, and then dry it at 80°C in a vacuum environment for 6h to obtain silica-polyacrylonitrile composite nano-microspheres.
[0043] S3. The silicon dioxide-polyacrylonitrile composite nano-microspheres obtained in step S2 are die-casted to form a layered aluminum sheet with a thickness of 80-300 μm, the aluminum sheet is put into a ball mill for grinding, and then put into a magnetic polishing machine with a rotation speed of 800 r / s for polishing, and finally sieved by a combined screening process of a linear vibrating screen and a sieve screen to sieve out a spray-free imitation metal masterbatch with a polyhedral structure with a particle size of 50-120 μm.
[0044] Example 4 The present embodiment provides an extruded spray-free ABS alloy material, which includes the following component raw materials in parts by weight: 85 parts of ABS resin, 12 parts of spray-free imitation metal masterbatch, 6.5 parts of toughening agent, 2.5 parts of compatibilizer, 0.4 parts of weathering agent, 0.8 parts of antioxidant, 0.8 parts of lubricant and 1.5 parts of dispersant.
[0045] The preparation method of the extruded spray-free ABS alloy material of the present embodiment comprises the following steps: in a nitrogen atmosphere, ABS resin, toughening agent, compatibilizer, weathering agent, antioxidant, lubricant and dispersant are mixed uniformly at 95°C for 3.5 hours in proportion and then added to the main feed port of the twin-screw extruder, and the spray-free imitation metal masterbatch is added from the side feed port of the twin-screw extruder in proportion, and the barrel temperature of the twin-screw extruder is controlled to be 230°C, the screw speed is 300rpm, and the vacuum degree is 0.06MPa, and the extruded spray-free ABS alloy material is obtained through melt blending and extrusion granulation. Among them, the middle position of the twin-screw extruder of the present embodiment is provided with a TME element and a ZME element, and the head position is provided with a toothed disk.
[0046] The method for preparing the spray-free imitation metal masterbatch of this embodiment comprises the following three steps S1-S3: S1. A silane coupling agent (prepared by mixing methyltriethoxysilane, acryltetraethoxysilane and dimethyldimethoxysilane in a mass ratio of 1:1:1) was mixed with anhydrous ethanol, and ammonia water (concentration of 25%), aluminum pigment and tetraethyl orthosilicate were added, and the mixture was stirred for 1 hour under a nitrogen atmosphere, and then the temperature was raised to 60°C and stirred for 3 hours, wherein the amount ratio of the silane coupling agent, anhydrous ethanol, ammonia water, aluminum pigment and tetraethyl orthosilicate was 6g:500mL:12mL:9g:7g; after the reaction was completed, the mixture was filtered, and the product was washed three times with anhydrous ethanol, and then dried at 80°C in a vacuum environment for 6 hours to obtain a modified silica-coated aluminum pigment; S2. The modified silica-coated aluminum pigment obtained in step S1 is subjected to copolymerization and cross-linking reaction with polyacrylonitrile resin to obtain silica-polyacrylonitrile composite nano-microspheres. The specific process is: add the modified silica-coated aluminum pigment to deionized water and stir evenly, add polyacrylonitrile resin, stir at 85°C for 3h, add initiator and cross-linking agent and continue stirring, wherein the amount ratio of modified silica-coated aluminum pigment, polyacrylonitrile resin, initiator and cross-linking agent is 110mg: 5mL: 90mg: 190mg; after the reaction is completed, cool to room temperature, filter, wash the product three times with anhydrous ethanol, and then dry it at 80°C in a vacuum environment for 6h to obtain silica-polyacrylonitrile composite nano-microspheres.
[0047] S3. The silicon dioxide-polyacrylonitrile composite nano-microspheres obtained in step S2 are die-casted to form a layered aluminum sheet with a thickness of 80-300 μm, the aluminum sheet is put into a ball mill for grinding, and then put into a magnetic polishing machine with a rotation speed of 800 r / s for polishing, and finally sieved by a combined screening process of a linear vibrating screen and a sieve screen to sieve out a spray-free imitation metal masterbatch with a polyhedral structure with a particle size of 50-120 μm.
[0048] Example 5 The present embodiment provides an extruded spray-free ABS alloy material, which includes the following component raw materials in parts by weight: 90 parts of ABS resin, 15 parts of spray-free imitation metal masterbatch, 8 parts of toughening agent, 3 parts of compatibilizer, 0.5 parts of weathering agent, 1 part of antioxidant, 1 part of lubricant and 2 parts of dispersant.
[0049] The preparation method of the extruded spray-free ABS alloy material of the present embodiment comprises the following steps: in a nitrogen atmosphere, ABS resin, toughening agent, compatibilizer, weathering agent, antioxidant, lubricant and dispersant are mixed uniformly at 100°C for 2h in proportion, and then added from the main feeding port of the twin-screw extruder, and the spray-free imitation metal masterbatch is added from the side feeding port of the twin-screw extruder in proportion, and the barrel temperature of the twin-screw extruder is controlled to be 230°C, the screw speed is 300rpm, and the vacuum degree is 0.06MPa, and the extruded spray-free ABS alloy material is obtained through melt blending and extrusion granulation. Among them, the middle position of the twin-screw extruder of the present embodiment is provided with a TME element and a ZME element, and the head position is provided with a toothed disk.
[0050] The method for preparing the spray-free imitation metal masterbatch of this embodiment comprises the following three steps S1-S3: S1. A silane coupling agent (prepared by mixing methyltriethoxysilane, acryltetraethoxysilane and dimethyldimethoxysilane in a mass ratio of 2:1:1) was mixed with anhydrous ethanol, and ammonia water (concentration of 25%), aluminum pigment and tetraethyl orthosilicate were added, and the mixture was stirred for 1 hour under a nitrogen atmosphere, and then the temperature was raised to 60°C and stirred for 3 hours, wherein the amount ratio of the silane coupling agent, anhydrous ethanol, ammonia water, aluminum pigment and tetraethyl orthosilicate was 8g:550mL:15mL:10g:8g; after the reaction was completed, the mixture was filtered, and the product was washed three times with anhydrous ethanol, and then dried at 80°C in a vacuum environment for 6 hours to obtain an aluminum pigment coated with modified silica; S2. The modified silica-coated aluminum pigment obtained in step S1 is subjected to copolymerization and cross-linking reaction with polyacrylonitrile resin to obtain silica-polyacrylonitrile composite nanospheres. The specific process is: add the modified silica-coated aluminum pigment to deionized water and stir evenly, add polyacrylonitrile resin, stir at 85°C for 3h, add initiator and cross-linking agent and continue stirring, wherein the amount ratio of modified silica-coated aluminum pigment, polyacrylonitrile resin, initiator and cross-linking agent is 120mg:6mL:100mg:200mg; after the reaction is completed, cool to room temperature, filter, wash the product three times with anhydrous ethanol, and then dry it at 80°C in a vacuum environment for 6h to obtain silica-polyacrylonitrile composite nanospheres.
[0051] S3. The silicon dioxide-polyacrylonitrile composite nano-microspheres obtained in step S2 are die-casted to form a layered aluminum sheet with a thickness of 80-300 μm, the aluminum sheet is put into a ball mill for grinding, and then put into a magnetic polishing machine with a rotation speed of 800 r / s for polishing, and finally sieved by a combined screening process of a linear vibrating screen and a sieve screen to sieve out a spray-free imitation metal masterbatch with a polyhedral structure with a particle size of 50-120 μm.
[0052] Comparative Example 1 This comparative example provides an extruded spray-free ABS alloy material, which adopts the same implementation as Example 1, and the difference from Example 1 is that the preparation method of the spray-free imitation metal masterbatch in this comparative example includes the following three steps S1-S3: S1. Mix dimethyldimethoxysilane with anhydrous ethanol, add ammonia water, aluminum pigment and tetraethyl orthosilicate, stir for 1 hour under nitrogen atmosphere, and then heat to 60°C and stir for 3 hours, wherein the amount ratio of dimethyldimethoxysilane, anhydrous ethanol, ammonia water (concentration of 25%), aluminum pigment and tetraethyl orthosilicate is 1g:200mL:5mL:5g:4g; filter after the reaction, wash the product with anhydrous ethanol three times, and then dry it under vacuum environment at 80°C for 6 hours to obtain modified silica-coated aluminum pigment; S2. The modified silica-coated aluminum pigment obtained in step S1 is subjected to copolymerization and cross-linking reaction with polyacrylonitrile resin to obtain silica-polyacrylonitrile composite nano-microspheres. The specific process is: add the modified silica-coated aluminum pigment to deionized water and stir evenly, add polyacrylonitrile resin, stir at 85°C for 3h, add initiator and cross-linking agent and continue stirring, wherein the amount ratio of modified silica-coated aluminum pigment, polyacrylonitrile resin, initiator and cross-linking agent is 70mg:3mL:60mg:150mg; after the reaction is completed, cool to room temperature, filter, wash the product three times with anhydrous ethanol, and then dry it at 80°C in a vacuum environment for 6h to obtain silica-polyacrylonitrile composite nano-microspheres.
[0053] S3. The silicon dioxide-polyacrylonitrile composite nano-microspheres obtained in step S2 are die-casted to form a layered aluminum sheet with a thickness of 80-300 μm, the aluminum sheet is put into a ball mill for grinding, and then put into a magnetic polishing machine with a rotation speed of 800 r / s for polishing, and finally sieved by a combined screening process of a linear vibrating screen and a sieve screen to sieve out a spray-free imitation metal masterbatch with a polyhedral structure with a particle size of 50-120 μm.
[0054] Comparative Example 2 This comparative example provides an extruded spray-free ABS alloy material, which adopts the same implementation as Example 1, and the difference from Example 1 is that no initiator is added in step S2 of the preparation method of the spray-free imitation metal masterbatch in this comparative example.
[0055] Comparative Example 3 This comparative example provides an extruded spray-free ABS alloy material, which adopts the same implementation as Example 1, and the difference from Example 1 is that the preparation method of the spray-free imitation metal masterbatch in this comparative example includes the following two steps S1-S2: S1. A silane coupling agent (prepared by mixing methyltriethoxysilane, acryltetraethoxysilane and dimethyldimethoxysilane in a mass ratio of 1:1:1) was mixed with anhydrous ethanol, and ammonia water (concentration of 25%), aluminum pigment and tetraethyl orthosilicate were added, and the mixture was stirred for 1 hour under a nitrogen atmosphere, and then the temperature was raised to 60°C and stirred for 3 hours, wherein the amount ratio of the silane coupling agent, anhydrous ethanol, ammonia water, aluminum pigment and tetraethyl orthosilicate was 3g:200mL:5mL:5g:4g; after the reaction was completed, the mixture was filtered, and the product was washed three times with anhydrous ethanol, and then dried at 80°C in a vacuum environment for 6 hours to obtain a modified silica-coated aluminum pigment; S2. The modified silica-coated aluminum pigment obtained in step S1 is subjected to copolymerization and cross-linking reaction with polyacrylonitrile resin to obtain a spray-free imitation metal masterbatch; the specific process is: the modified silica-coated aluminum pigment is added into deionized water and stirred evenly, the polyacrylonitrile resin is added, stirred at 85°C for 3 hours, and the initiator and cross-linking agent are added and stirred continuously, wherein the amount ratio of the modified silica-coated aluminum pigment, polyacrylonitrile resin, initiator and cross-linking agent is 70mg:3mL:60mg:150mg; after the reaction is completed, it is cooled to room temperature, filtered, and the product is washed three times with anhydrous ethanol, and then dried at 80°C in a vacuum environment for 6 hours to obtain silica-polyacrylonitrile composite nano-microspheres, which are the spray-free imitation metal masterbatch.
[0056] Comparative Example 4 This comparative example provides an extruded spray-free ABS alloy material, which adopts the same implementation as Example 1, and the difference from Example 1 is that no cross-linking agent is added in step S2 of the preparation method of the spray-free imitation metal masterbatch in this comparative example.
[0057] Comparative Example 5 This comparative example provides an extruded spray-free ABS alloy material, which adopts the same implementation as Example 1, and the difference from Example 1 is that commercially available metal masterbatch is used in this comparative example instead of the spray-free imitation metal masterbatch prepared in Example 1.
[0058] Test Case The extruded spray-free ABS alloy materials of the above Examples 1-5 and Comparative Examples 1-5 were subjected to high and low temperature deformation tests (low temperature is -40°C, high temperature is 70°C), low temperature (-40°C) cantilever beam notched impact strength test, detergent resistance test, and appearance test. The test results are shown in Table 1. Among them: (1) The test method for detergent corrosion resistance is as follows: use extruded spray-free ABS alloy material to prepare type 1A tensile specimens (total length 150 mm) specified in GB / T1040.2, prepare a total of 10 specimens and place the 10 specimens on a fixture with a length of 145 mm, keeping the specimens in a bending stress state; then apply detergent to the bending parts of 5 of the stressed specimens, and use the other 5 specimens without detergent as a control, and then wrap them with a stretch film. After 48 hours of testing, use an electronic tensile testing machine to test the tensile strength T0 of the ABS specimens without detergent and the tensile strength T1 of the ABS specimens with detergent applied according to GB / T1040.2, and calculate the tensile strength retention rate of the 5 ABS specimens with detergent applied according to the formula T1*100 / T0; (2) Appearance test: ① The extruded spray-free ABS alloy materials of the above Examples 1-5 and Comparative Examples 1-5 were made into standard samples (30 cm*50 cm), and then the number of pits ≥0.1 mm on the samples was counted under an environmental scanning electron microscope and a microscope; ② The extruded spray-free ABS alloy materials of the above Examples 1-5 and Comparative Examples 1-5 were made into 100 standard samples (30 cm*90 cm*0.25 mm), and then the number of flow mark weld lines on each standard sample was counted under a fluorescent lamp to obtain the flow mark weld line scrap rate; (3) High and low temperature deformation test: The extruded spray-free ABS alloy materials of the above Examples 1-5 and Comparative Examples 1-5 were made into standard specimens (30 cm*50 cm), and stored at low temperature (-40°C) and high temperature (70°C) for 72 hours, respectively, to observe the changes in the specimen gap.
[0059] Table 1 Performance test results
[0060] According to the results in Table 1, we can see that: Compared with Comparative Example 5, the extruded spray-free ABS alloy materials prepared in Examples 1-5 have a lower scrap rate of flow mark weld lines and a lower number of pits, which indicates that the spray-free metal-imitation masterbatch of the present invention can solve the defects of flow mark weld lines, pits, etc. existing in the ABS alloy materials; the extruded spray-free ABS alloy materials prepared in Examples 1-5 can still maintain a higher tensile retention rate after the detergent corrosion resistance test, and the high and low temperature deformation gap is not obvious, which indicates that the spray-free metal-imitation masterbatch of the present invention can prevent chemical reagents such as oil stains from reacting with rubber molecules to cause aging, and can improve the mechanical properties and stability of the spray-free ABS alloy materials, and improve the high and low temperature deformation resistance of the materials; Compared with Example 1, Example 2 and Example 4, Example 1 uses a small amount of silane coupling agent when preparing the spray-free imitation metal masterbatch, which does not sufficiently modify the silicon dioxide on the surface of the aluminum pigment. When copolymerized and cross-linked with polyacrylonitrile, a complete network structure of O-Si-O functional groups and cyano groups cannot be formed on the surface of the aluminum pigment, resulting in a significant increase in the scrap rate of flow mark weld lines, a significant decrease in the tensile retention rate after the detergent corrosion test, and a significant increase in the number of pits; while Example 2 does not copolymerize with acrylonitrile when preparing the spray-free imitation metal masterbatch. The comparative example 4 was not cross-linked with acrylonitrile when preparing the spray-free imitation metal masterbatch. The comparative examples 2 and 4 could not form a network structure of O-Si-O functional groups and cyano groups interwoven on the surface of the aluminum pigment, resulting in a significant increase in the scrap rate of the flow mark weld line, a significant decrease in the tensile retention rate after the detergent corrosion test, a significant increase in the number of pits, and a significant increase in the high and low temperature deformation gap; this shows that the acrylonitrile grafted aluminum powder coating layer can improve the compatibility of ABS resin and aluminum powder, and reduce appearance defects such as flow mark weld lines, pits, and pits; Example 1 is compared with Comparative Example 3: Comparative Example 3 did not perform die casting, ball milling, and polishing when preparing the spray-free imitation metal masterbatch, and did not form a polyhedron structure, resulting in a significant increase in the scrap rate of flow marks and weld lines; this shows that the polyhedron structure of the spray-free imitation metal masterbatch plays a key role in eliminating the appearance defects of the material such as pits, flow marks and weld lines.
[0061] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0062] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a spray-free imitation metal masterbatch, characterized in that: It includes the following steps: S1. After mixing the silane coupling agent with anhydrous ethanol, adding ammonia, aluminum pigment, and tetraethyl orthosilicate, stirring and mixing under a protective atmosphere, heating the reaction, filtering, washing, and drying to obtain a modified silica-coated aluminum pigment; S2. The modified silica-coated aluminum pigment is copolymerized and cross-linked with a polyacrylonitrile resin to obtain silica-polyacrylonitrile composite nanospheres; S3. The silicon dioxide-polyacrylonitrile composite nano-microspheres are die-cast to form a layered aluminum sheet, and the aluminum sheet is ground, polished, and sieved to obtain a spray-free imitation metal masterbatch with a polyhedral structure.
2. The method for preparing the spray-free imitation metal masterbatch according to claim 1, characterized in that: In step S1, the silane coupling agent includes at least one of methyltriethoxysilane, acryltetraethoxysilane, and dimethyldimethoxysilane.
3. The method for preparing the spray-free imitation metal masterbatch according to claim 2, characterized in that: The silane coupling agent comprises methyltriethoxysilane, acryltetraethoxysilane and dimethyldimethoxysilane, and the mass ratio of the methyltriethoxysilane, the acryltetraethoxysilane and the dimethyldimethoxysilane is 1-3:1:
1.
4. The method for preparing the spray-free imitation metal masterbatch according to claim 1, characterized in that: In step S1, the usage ratio of the silane coupling agent, anhydrous ethanol, ammonia water, aluminum pigment and tetraethyl orthosilicate is 3-8 g: 200-550 mL: 5-15 mL: 5-10 g: 4-8 g, and the concentration of the ammonia water is 25%.
5. The method for preparing the spray-free imitation metal masterbatch according to claim 1, characterized in that: In step S1, the heating reaction is carried out by stirring at 40-60° C. for 2-4 hours, and the drying is carried out by drying at 80-85° C. in a vacuum environment for 5-7 hours.
6. The method for preparing the spray-free imitation metal masterbatch according to claim 1, characterized in that: In step S2, the copolymerization and cross-linking reaction includes the following steps: adding the modified silica-coated aluminum pigment into deionized water and mixing evenly, adding polyacrylonitrile resin, heating and stirring, then adding initiator and cross-linking agent and continuously stirring, after the reaction is completed, cooling to room temperature, filtering, washing and drying to obtain silica-polyacrylonitrile composite nanospheres.
7. The method for preparing the spray-free imitation metal masterbatch according to claim 6, characterized in that: The dosage ratio of the modified silica-coated aluminum pigment, polyacrylonitrile resin, initiator and cross-linking agent is 70~120mg:3~6mL:60~100mg:150~200mg, the molecular weight of the polyacrylonitrile resin is 100,000~300,000, the heating and stirring is stirring at 80~95°C for 2~4h, and the drying is drying at 80~85°C in a vacuum environment for 5~7h.
8. The method for preparing the spray-free imitation metal masterbatch according to claim 1, characterized in that: In step S3, the thickness of the aluminum sheet is 80-300 μm; And / or, in step S3, the screening is performed by a combined screening process of a linear vibrating screen and a sieve to obtain a spray-free imitation metal masterbatch with a polyhedral structure and a particle size of 50 to 120 μm.
9. A spray-free imitation metal masterbatch, characterized in that: The metal masterbatch is prepared by the method for preparing the spray-free metal-imitation masterbatch according to any one of claims 1 to 8.
10. An extruded spray-free ABS alloy material, characterized in that: The invention is prepared from the following components in parts by weight: 70-90 parts of ABS resin, 5-15 parts of the spray-free imitation metal masterbatch as claimed in claim 9, 2-8 parts of toughening agent, 1-3 parts of compatibilizer, 0.1-0.5 parts of weathering agent, 0.2-1 parts of antioxidant, 0.2-1 parts of lubricant and 0.5-2 parts of dispersant.
11. The extruded spray-free ABS alloy material according to claim 10, characterized in that: The ABS resin is an acrylonitrile-butadiene-styrene copolymer, which is obtained by mixing an acrylonitrile-butadiene-styrene copolymer prepared by an emulsion method and an acrylonitrile-butadiene-styrene copolymer prepared by a bulk method in a mass ratio of 3:
1.
12. The extruded spray-free ABS alloy material according to claim 10, characterized in that: The toughening agent is a styrene-ethylene-butylene-styrene block copolymer; and / or, the compatibilizer is a carboxylic acid grafted compatibilizer; and / or, the antioxidant is a hindered phenol antioxidant; and / or, the lubricant is lubricant TAS-2A; and / or, the dispersant is a polymethacrylic acid derivative dispersant; and / or, the weathering agent is a benzotriazole weathering agent.
13. A method for preparing an extruded spray-free ABS alloy material as claimed in any one of claims 10 to 12, characterized in that: It includes the following steps: Under a protective atmosphere, ABS resin, toughening agent, compatibilizer, weathering agent, antioxidant, lubricant and dispersant are mixed evenly in proportion and added to the main feeding port of the extruder. The spray-free imitation metal masterbatch is added to the side feeding port of the extruder in proportion. After melt blending and extrusion granulation, the extruded spray-free ABS alloy material is obtained.
14. The method for preparing the extruded spray-free ABS alloy material according to claim 13, characterized in that: The ABS resin, toughening agent, compatibilizer, weathering agent, antioxidant, lubricant and dispersant are mixed at a temperature of 80° C. to 100° C. and for a mixing time of 2 to 4 hours.
15. The method for preparing the extruded spray-free ABS alloy material according to claim 13, characterized in that: The extruder is a twin-screw extruder, the barrel temperature of the extruder is 200° C. to 230° C., the screw speed is 200 to 300 rpm, and the vacuum degree is 0.06 to 0.1 MPa.
16. The method for preparing the extruded spray-free ABS alloy material according to claim 13, characterized in that: The middle position of the extruder is provided with a TME element and a ZME element, and the head position is provided with a toothed disk.
Citation Information
Patent Citations
High weather-resistant spray-free metal-imitating ABS composite material
CN107163493A
Easy-to-clean spraying-free ABS / PMMA alloy material and preparation method thereof
CN110819061A
Non-spray resin, and preparation method and use therefor
WO2023174060A2